2016
DOI: 10.1371/journal.pone.0168968
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Synthetic CRISPR Reagents as a Tool for Arrayed Functional Genomic Screening

Abstract: To date, lentiviral-based CRISPR-Cas9 screens have largely been conducted in pooled format. However, numerous assays are not amenable to pooled approaches, and lentiviral screening in arrayed format presents many challenges. We sought to examine synthetic CRISPR reagents in the context of arrayed screening. Experiments were performed using aberrant DNA replication as an assay. Using synthetic CRISPR RNAs targeting the known control gene GMNN in HCT-116 cells stably expressing Cas9, we observed statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…For this reason, an important prerequisite for these screens would be to be able to transfect low number of cells with minimal cytotoxicity. We have observed that with liquid transfection some cell lines such as RPE‐1 can be efficiently transfected when low number of cells was seeded (2,500 cells/well) as previously reported in the literature for other cell lines (Tan & Martin, ; Strezoska et al , ; de Groot et al , ). However, some cell lines such as NCI‐H358, NCI‐N87, or HEK293T that also express doxycycline‐inducible Cas9 (Fig EV1) suffer from increased cytotoxicity and high variability under the same conditions.…”
Section: Resultssupporting
confidence: 74%
“…For this reason, an important prerequisite for these screens would be to be able to transfect low number of cells with minimal cytotoxicity. We have observed that with liquid transfection some cell lines such as RPE‐1 can be efficiently transfected when low number of cells was seeded (2,500 cells/well) as previously reported in the literature for other cell lines (Tan & Martin, ; Strezoska et al , ; de Groot et al , ). However, some cell lines such as NCI‐H358, NCI‐N87, or HEK293T that also express doxycycline‐inducible Cas9 (Fig EV1) suffer from increased cytotoxicity and high variability under the same conditions.…”
Section: Resultssupporting
confidence: 74%
“…Some groups have previously attempted to develop arrayed CRISPR screens (Hultquist et al 2016;McCleland et al 2016;Tan and Martin 2016;Datlinger et al 2017;Strezoska et al 2017). These studies were based on guide RNA libraries consisting of individual lentiviral sgRNAs for single genes or synthesized CRISPR RNA (crRNA) in a manner similar to siRNA screens.…”
mentioning
confidence: 99%
“…However, correlation analysis between KIAA1377 expression versus clinicopathological variables revealed that there was a significant correlation of KIAA1377 expression with lymph nodes metastases, which leads to the suggestion that KIAA1377 might be involved in the lymph node metastasis of ESCC cells. The slight discrepancy between in vivo and in vitro prompted us to rework the biological roles of KIAA1377 implicated in the proliferation and motility of SCC cells by using the alternative CRISPR‐Cas9 technique (Shalem et al, ), which is distinctively different from the shRNA system in the case of silencing efficiency (Tan and Martin, ; Wang et al, ). In the current observation, knock‐out of KIAA1377 mediated by the CRISPR‐Cas9 system turns out to be able to markedly slow down the growth and motility of KYSE‐150 and HeLa cells, preliminarily defining the oncogenic roles of KIAA1377 in SCC cells.…”
Section: Discussionmentioning
confidence: 99%